Microbiota, Gut Health and Chicken Productivity: What Is the Connection? - Diaz Carrasco, Juan M. (Microorganisms, 2019)
Gut microbiota and its relationship to animal health and productivity in commercial broiler chickens has been difficult to establish due to high variability between flocks, which derives from plenty of environmental, nutritional, and host factors that influence the load of commensal and pathogenic microbes surrounding birds during their growth cycle in the farms. Chicken gut microbiota plays a key role in the maintenance of intestinal health through its ability to modulate host physiological functions required to maintain intestinal homeostasis, mainly through competitive exclusion of detrimental microorganisms and pathogens, preventing colonization and therefore decreasing the expense of energy that birds normally invest in keeping the immune system active against these pathogens. Therefore, a “healthy” intestinal microbiota implies energy saving for the host which translates into an improvement in productive performance of the birds. This review compiles information about the main factors that shape the process of gut microbiota acquisition and maturation, their interactions with chicken immune homeostasis, and the outcome of these interactions on intestinal health and productivity.